APLIKASI SISTEM INFORMASI GEOGRAFIS KOS DI PALANGKA RAYA BERBASIS ANDROID - Sahay, Abertun Sagit (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2020)
Usage of Android Smartphone in home boarding information can give big benefit. If it is compared with searching of home boarding location manually, search with the application has some surplus, such as: a user can search through android smartphone everytime and everywhere, and also can see the detail of home boarding information. Search of home boarding in Palangka Raya city is still executed manually, alike search of home boarding location directly, if it’s not match, the seeker must search manually over and over again. For developing a geographic information system of home boarding search for Palangka Raya area that can find the nearest location, The Methodologhy used is Waterfall methodologhy that has 5 steps: (1) requirement: Actors those are administrator, home boarding owner and visitors. some of data are photo, latitude and longitude, and home boarding information. (2) Design System: design system in this research used UML(Unified Modeling Language). (3) Coding & Testing: this step used Java Programming, Database MySQL and XAMPP and using Haversine Algorithm for home boarding searching. (4) Integration & Testing, Testing of all system used Blackbox testing. (5) Operation and Maintanance, this step for seeing change that is needed for fungtionalization of development. According to developing of geographic information system of home boarding search. The conclusion are the user can know the nearest home boarding location from user’s position with using radius feature that used haversine algorithm, the owner of home boarding manage directly with giving original information and the application also help the owner on home boarding marketing. The application is expected to be developed as adding push notification feature